Description of Smoking Behavior in Adolescents During The Covid-Pandemic - Irja Sriani Masitha; DWI RAMADINI; Muhammad Fanny Afriansyah; Muhammad Herlangga Putra (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The behaviors that young people exhibit in the COVID-19 era are the strong behaviors in which the four information ants interviewed have different behaviors in the experience, expectations, the number of cigarettes, and the type of cigarettes consumed. Smoking behavior is one form of behavior encountered in people's lives and can be found in various places such as in crowded places, streets, city buses, hospitals, schools, and so on. A smoking habit can cause damage to the lungs and airways that will cause diseases of the respiratory system, such as chronic bronchitis, emphysema, even lung cancer. Schools and People need to be involved in efforts to prevent and intervene in adolescent smoking behavior more intensively.